Mechanisms for radical reactions initiating from N-hydroxyphthalimide esters - Azpilcueta-Nicolas, Carlos R.; Lumb, Jean-Philip (Beilstein Journal of Organic Chemistry, 2024)
Due to their ease of preparation, stability, and diverse reactivity, N-hydroxyphthalimide (NHPI) esters have found many applications as radical precursors. Mechanistically, NHPI esters undergo a reductive decarboxylative fragmentation to provide a substrate radical capable of engaging in diverse transformations. Their reduction via single-electron transfer (SET) can occur under thermal, photochemical, or electrochemical conditions and can be influenced by a number of factors, including the nature of the electron donor, the use of Brønsted and Lewis acids, and the possibility of forming charge-transfer complexes. Such versatility creates many opportunities to influence the reaction conditions, providing a number of parameters with which to control reactivity. In this perspective, we provide an overview of the different mechanisms for radical reactions involving NHPI esters, with an emphasis on recent applications in radical additions, cyclizations and decarboxylative cross-coupling reactions. Within these reaction classes, we discuss the utility of the NHPI esters, with an eye towards their continued development in complexity-generating transformations.
Keywords: decarboxylative couplings; mechanisms; NHPI-esters; radical reactions